Imaging Review of Skeletal Tumors of the Pelvis Malignant Tumors and Tumor Mimics - Gandikota Girish; Karen Finlay; David Fessell; Deepa Pai; Qian Dong; David Jamadar (The Scientific World Journal)
Malignant lesions of the pelvis are not uncommon and need to be differentiated from benign lesions and tumor mimics. Appearances are sometimes nonspecific leading to consideration of a broad differential diagnosis. Clinical history, anatomic location, and imaging characterization can help narrow the differential diagnosis. The focus of this paper is to demonstrate the imaging features and the role of plain films, computed tomography, and magnetic resonance imaging for detecting and characterizing malignant osseous pelvic lesions and their common mimics.